Сборник вопросов и задач по физической химии для самоконтроля: учебное пособие - Атанасянц А. Г. Анатолий Георгиевич; Белевский С. Ф. Станислав Федорович; Каретников Г. С. Герман Сергеевич; Никитин К. Н. Кирилл Николаевич; Старастенко Е. П. Екатерина Павловна (Москва, Высшая школа, 1979)
Авт. указаны на обороте тит. л.